Performances of Automated Control System of Membrane Gas Absorption: Optimization Study - Sunarti, Abd Rahman; A. L., Ahmad (Department of Chemical Engineering, Diponegoro University, 2015)
Membrane gas absorption (MGA) can overcome the major drawbacks of the processes that have been used commercially for the removal of CO2. Using produced thin film composite (TFC) membrane, performances of automated control system of MGA was optimized using central composite design (CCD) of Response Surface Methodology (RSM). ANOVA result showed that the temperature, concentration, velocity and flow rate of DEA played a significant role. The optimum DEA temperature was found at 50oC, DEA concentration at 2M, velocity at 3770m/s and 80 ml/min of DEA flow rate with 0.90 of desirability.